Acromioplasty rates in patients with shoulder disorders with and without acupuncture treatment: a retrospective propensity score–matched cohort study. Issue 4 (August 2020) - Yang, Gujin; Jung, Boyoung; Kim, Me-riong; Koh, Wonil; Kim, Namkwen; Lee, Eun-Kyoung; Ha, In-Hyuk
Objective: This retrospective propensity score–matched cohort study aimed to examine the frequency of acromioplasty among patients with shoulder disorders receiving and not receiving acupuncture, based on Korea National Health Insurance Service-National Sample Cohort (NHIS-NSC) data. Methods: We included cases of high-frequency shoulder disorders—adhesive capsulitis, rotator cuff syndrome, shoulder impingement syndrome, and sprain and strain of the shoulder joint—stratified from the Korea NHIS-NSC database between 2002 and 2013; cases were classified into two groups based on a history of acupuncture treatment performed at least twice within 6 weeks (acupuncture group: n = 111, 561; control group: n = 71, 340). We examined propensity scores and hazard ratios (HRs) for the frequency of acromioplasty, within 2 years of the first treatment or first examination in the acupuncture and control groups, respectively; cumulative survival rates were estimated using Kaplan–Meier survival analysis. Results: Following propensity score matching, no differences were observed between the acupuncture and control groups for variables including sex, age, income and the Charlson comorbidity index. In addition, the incidence rates of acromioplasty within 2 years were lower in the acupuncture group than in the control group (HR 0.264; 95% confidence interval 0.224–0.311). Based on differences in sensitivity analyses for the numbers of acupuncture sessions and treatment duration, the frequency of acromioplasty within 2 years was lower in the acupuncture group than in the control group. Conclusion: This study found that the frequency of acromioplasty was reduced in patients with shoulder disorders who had been treated with acupuncture. Although the findings need to be verified by prospective randomized clinical trials, these results imply that acupuncture may be effective at reducing the incidence rate of shoulder surgery.